Anxiolytic and antidepressant effects of tarragon (Artemisia dracunculus L.) hydro-alcoholic extract in male rats exposed to chronic restraint stress - Hajar Khosravi (یافته‌های نوین در علوم زیستی, 2017)
Tarragon (Artemisia dracunculus L.) has antioxidant, anti-diabetic, anti-bacterial and anti-inflammatory proper-ties. The aim of this study was to evaluate the effect of tarragon hydro-alcoholic extract on anxiety and depression in male rats exposed to chronic restraint stress. Forty eight male rats were randomly divided into six groups including 1) control, 2) stress, 3) tarragon 100, 4) tarragon 500, 5) stress-tarragon 100 and 6) stress-tarragon 500. Groups 2, 5, and 6 were placed in restrainer for 21 consecutive days, 6 hours a day. Groups 3, 4, 5, and 6 were gavaged with tarragon extract of different do-ses (100 and 500mg/kg). At the end of this 21-day period, anxiety and depression were evaluated by elevated plus maze and forced swimming test. Data analysis was performed using one-way ANOVA, p<0.05 being considered significant. The pe-rcentages of open arm entry and time spent in open arm increased significantly in tarragon-stress groups compared with st-ress group (p<0.05). Tarragon extract decreased significantly the immobility time in rats exposed to stress in forced swim-ming test (p<0.01). The results suggested that hydro-alcoholic extract of Artemisia dracunculus L. reduced the anxiety and depression in rats exposed to chronic immobilization stress, probably due to its anti-oxidant compounds